O regime de metas de inflação: o debate entre ortodoxos e heterodoxos - Campedelli, André Luis (2014)
The objective of this work is to conduct an analysis about the current debate around the inflation target in the Brazilian case. The justification for this work is to highlight the importance the monetary policy has in the economic growth of a country. Nevertheless, it is little used for this purpose in the Brazilian case, being used only for the inflation control. After an introduction, which punctuates the main work points, a theoretical survey about the monetary policy discussion that happened in the XX century is carried out, whose final result is the development of inflation target. A historical-analytical analysis for the Brazilian case since the adoption of the inflation target until 2013 is performed next, reflecting upon the results obtained and the measures for the acquisition of these, in addition to an analysis about the consequences of the measures during this period. The last part of this work puts into discussion the current situation of this policy in Brazil, bringing up the main points observed by orthodox and heterodox economists. A balance of all the analyzed ideas is done, and in the conclusion the main points considered relevant for the current debate about the inflation target in Brazil are posed and covered